Optimization of Dikmas Kamsel Unit to Prevent Traffic Violations in the Era of Society 5.0 in the Jurisdiction of Karanganyar (Advances in Police Science Research Journal, 2024)
Increased traffic violations become a problem that has an impact on the security, safety and smoothness of traffic. An action that is right on target is also needed to be preventive in nature to the public by conveying traffic orderly messages that aim to raise and increase public awareness in traffic. In this case, the role of the Kamsel Unit through Community Education (Dikmas) activities is very much needed as the spearhead of preventing traffic violations to provide education to the public about the importance of orderly traffic by adjusting the development of an active society in the use of technology in the era of society 5.0. The purpose of this study was to determine the extent to which the implementation of Dikmas Then Kamsel Unit of the Karanganyar Police in order to prevent traffic violations. This research is a qualitative research with data collection techniques by observation, interviews, and document study. The results of this study indicate that the Kamsel Unit of Karanganyar Police needs to optimize the activities of Dikmas Lantas through applicable problem solving steps in the form of internal organizational improvements, Kamsel Unit officers are expected to be able to improve their ability to deliver orderly traffic messages with the support of cross-unit personnel and functions so as to provide maximum education to the public. Supported by technological breakthroughs and innovations in the form of the Smart Zebra application by the author in improving the quality of Traffic Education by applying conventional and modern community service methods.
Keywords: Pelanggaran Lalu Lintas; Dikmas Lantas; Smart Zebra